PNAS envy? - Duncan Hull (2008)
The United States National Academy of Sciences (NAS) is an "honorific society of distinguished scholars engaged in scientific and engineering research, dedicated to the furtherance of science and technology and to their use for the general welfare". Set up by none other than Abraham Lincoln himself, the academy publishes a prestigious scientific journal, called the […]